1984
DOI: 10.1007/bf00429761
|View full text |Cite
|
Sign up to set email alerts
|

The physiological role of malic enzyme in grape ripening

Abstract: The high specificity of malic enzyme (ME; EC 1.1.1.40) from grape berries (Vitis vinifera L.) for the naturally occurring L-enantiomer of malic acid, its very selective C4-decarboxylation, and certain allosteric properties, reported previously, favour the conjecture of a regulatory function of ME in fruit malic acid degradation. On the other hand, high ME activity was detected even during the acid-accumulating phase of berry development. Also, the in vitro reversibility of the reaction supports the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…It is suggested that in fruit ripening, NADP-ME may produce the respiratory substrates pyruvate and NADPH from malate and NADP + (Ruffner, 1982;Drincovich et al, 2001) in cytosol and maybe thus partake in malate degradation during ripening (Ruffner et al, 1984;Franke and Adams, 1995). Here, feeding experiments involving the incubation of positionally labeled Glcs showed that the strong decrease in plastidic NADP-ME levels did not lead to substantial changes in overall respiration rates and TCA cycle flux in tomato fruits.…”
Section: Effects Of Cytosolic Pepck and Plastidic Nadp-me On Starch Bmentioning
confidence: 77%
“…It is suggested that in fruit ripening, NADP-ME may produce the respiratory substrates pyruvate and NADPH from malate and NADP + (Ruffner, 1982;Drincovich et al, 2001) in cytosol and maybe thus partake in malate degradation during ripening (Ruffner et al, 1984;Franke and Adams, 1995). Here, feeding experiments involving the incubation of positionally labeled Glcs showed that the strong decrease in plastidic NADP-ME levels did not lead to substantial changes in overall respiration rates and TCA cycle flux in tomato fruits.…”
Section: Effects Of Cytosolic Pepck and Plastidic Nadp-me On Starch Bmentioning
confidence: 77%
“…It is possible but unlikely that carboxylation is occumng via pyruvate carboxylase, PEP carboxykinase or malic enzyme. In plants, malic enzyme seems only to function unidirectionally toward pyruvate formation, decarboxylating malate (Ruffner et al, 1984). Pyruvate carboxylase conversion of pyruvate to OAA does not seem to occur in plants (Lance and Rustin, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In such situations, tonoplast leakage is likely to increase as membranes have been proposed to be the sites of damage [123] and when it does, the leakage becomes prime cause of malate vacuolar decompartmentation resulting changes in malic acid [124]. As a result of malic acid breakdown, pH of the cell sap increases during ripening [125] and becomes abnormally high in sunlit berries [126]. This explains the high pH of sunburned berries, which was same as reported for sunexposed Merlot berries [127].…”
Section: Compositional Changes In Disordered Berriesmentioning
confidence: 99%